Efek Pemberian Dosis Berulang dan Dosis Tunggal Ekstrak Kulit Batang Cempedak (Artocarpus Champeden Spreng.) Pada Mencit Terinfeksi Plasmodium Berghei - SOFIANA SARI; ACHMAD FUAD HAFID; ATY WIDYAWARUYANTI (JURNAL ILMU KEFARMASIAN INDONESIA, 2015)
Artocarpus champeden Spreng. (Moraceae) known as “cempedak”, was traditionally used for antimalarial remedies in Indonesia. Study to determine antimalarial activity of ethanol extract of cempedak stembark was carried out. Artocarpus champeden Ethanol Extract (ACEE) was administered twice per day (multiple dose) and once per day (single dose) orally. The study was carried out by modification method of the “4 Days Suppressive Test” originally described by Peter. The result showed that ACEE administered twice per day inhibited parasites growth (ED 0.19 mg/kg BW) higher than once per day (ED 6.0 mg/kg BW) and 10 mg/kg body weight of dose administrated twice per day was more effective than 100 mg/kg body weight once per day.